Towards More Sustainable Cities: Tools and Policies for Urban Goods Movements - Antonio Comi; Gianfranco Fancello; Francesco Piras; Patrizia Serra (Journal of Advanced Transportation)
Although urban freight transportation is crucial to address societal demands, it also has a major negative impact on the environment, the economy, and society. Then, the growing interest in promoting more sustainable and liveable cities is pushing to point out more in depth the role of urban goods movements within the planning process, as well as city administrators to implement new sustainable city logistics actions/policies/measures. Therefore, after a brief overview, the study presents more advanced techniques (models and methodologies) to help in the assessment of planning scenario. This paper concentrates on the importance of urban freight transport and logistics. Then, technical and logistics actions are outlined, and future last-mile delivery challenges are discussed. The main objective is to support urban planners, on a strategic and tactical scale, in obtaining an overview of urban freight transport systems that point out the challenges for implementing sustainable city logistics scenarios. It is also of interest to technicians because they can identify the most suitable methodologies, as well as the features that they need for selecting and assessing ex ante the effects of city logistics measures. This work is useful for researchers in various sectors because it allows them to formalise and then to solve the problems for simulating the complex system of urban goods movements where there are different actors with own interests that are conflicting.